First report of steroid derivatives isolated from starfish Acanthaster planci with anti-bacterial, anti-cancer and anti-diabetic activities. Issue 21 (1st November 2022) - Abd El Hafez, Mohamed S.M.; Aziz Okbah, Mohamed Abd El; Ibrahim, Hassan A.H.; Hussein, Ahmed Abd El Rahim; El Moneim, Nadia Ahmed Abd; Ata, Athar
Abstract: Chemical studies on Acanthaster planci have afforded two steroids, 5α-cholesta-24-en-3β, 20β-diol-23-one (1 ) and 5α-cholesta-9(11)-en-3β, 20β-diol (2 ). Structures compounds 1 and 2 were determined with the help of spectroscopic studies. Compound 1 showed strong antibacterial activity (21.0 ± 0.06 mm) against P. aeruginosa . Compounds 1 and 2 were also active against human breast carcinoma cells (MCF-7) with LC50 values of 49 ± 1.6 and 57.5 ± 1.5 μg/ml, respectively. This bioactivity was comparable to the currently used anticancer agent, cisplatin (LC50 46 ± 1.1 µg/ml). Compounds 1 and 2 exhibited anti-α-glucosidase activity with IC50 values of 58 ± 0.8 and 55 ± 0.5 µg/ml, respectively, whereas IC50 of Acarbose as a positive control was found to be 36 ± 0.4 µg/ml in our bioassay. Graphical Abstract: UF0001